تقييم أداء خوارزميات جدولة المهام في الحوسبة السحابية - قبلان, قاسم; ديب, حازم (Latakia University Journal -Engineering Sciences Series, 2018)
Cloud computing infrastructure is suitable for meeting computational needs of large task sizes. Optimal scheduling of tasks in cloud computing environment has been proved to be an NP-complete problem, hence the need for the application of heuristic methods. Several algorithms have been developed and used in addressing this problem, but choosing the appropriate algorithm for solving task assignment problem of a particular nature is difficult since the methods are developed under different assumptions. Therefore, Four rule based algorithms are implemented and used to schedule autonomous tasks in homogeneous environment with the aim of comparing their performance in terms of cost, degree of imbalance, makespan, throughput , resource utilization and Quality of Service. Optimized First Come First Served algorithm (OFCFS), Minimum Completion Time algorithm (MCT), Sufferage algorithm and Inter Cloud Scheduling with Priority using PTC Algorithm (ICSPPTC) are the heuristic algorithms considered for the performance evaluation and analysis of task scheduling in cloud computing. تعتبر البنية التحتية للحوسبة السحابية مناسبة لتلبية الاحتياجات من الموارد الحاسوبية و التي تطلبها المهام الكبيرة . ولقد ثبت أن عملية جدولة المهام في بيئة الحوسبة السحابية بشكل أمثلي هي مشكلة من تعقيد NP-Complete . ومن هنا برزت الحاجة إلى تطبيق أساليب الاستدلال . تم اقتراح عدد من خوارزميات الجدولة واستخدامها في معالجة هذه المشكلة، ولكن اختيار الخوارزمية المناسبة لحل مشكلة جدولة مهمات مختلفة لكل منها طبيعة معينة يعتبر أمراً صعباً و ذلك لأن تلك الخوارزميات يتم تطويرها في إطار ظروف و بيئات مختلفة. لذلك تم تطبيق واستخدام أربع خوارزميات لجدولة المهام المستقلة في بيئة متجانسة بهدف مقارنة أدائها من حيث الكلفة Cost، ودرجة عدم التوازن Degree of Imbalance ، و زمن التنفيذ الكلي لمجموعة من المهام Makespan ، و الإنتاجية Throughput، واستخدام الموارد Resource Utilization وجودة الخدمة Quality of Service . خوارزمية القادم أولاً يُخدَّم أولاً المحسنة Optimized FCFS (OFCFS) و خوارزمية زمن الانتهاء الأدنى Minimum Completion Time (MCT) و خوارزمية المعاناة (Sufferage) و خوارزمية الجدولة مع الأولوية بالاعتماد على قوة الاختيار الثنائي Inter Cloud Scheduling with Priority using PTC Algorithm (ICSPPTC) هي الخوارزميات التي تمت مناقشتها من أجل تقييم أداء و تحليل عملية جدولة المهام في الحوسبة السحابية .